Mendeskripsikan Peran Pendidikan Tinggi dalam Menyiapkan Sumber Daya Manusia Menghadapai Era Manajemen 5.0 - Rochaya, Siti; Asmanah, Siti; Suharyat, Yayat (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This article aims to show the role of universities in increasing the competitiveness of human resources in the era of society 5.0. A university is an organization that has a mission to educate the nation. Higher education plays an important role in producing the nation's next generation, therefore a quality university is capable of producing a superior generation. In reality, the competitiveness of higher education institutions in Indonesia is still low. The research used is qualitative with a phenomenological approach. The results of the research show that the competitiveness of higher education institutions is still low compared to other countries, and the quantity and quality of human resource development is still low. Therefore, the role of the Human Resources development division at the university is important. There is a need to improve the management system as in the other countries which can be emulated to produce quality higher education resources.